The Effect of Home Care Service Quality on Patient Satisfaction - Zusana A. Sasarari; Viyan Septiyana Achmad; Ali Syahid Bayau Naka; Nur Andani (Jurnal Edukasi Ilmiah Kesehatan, 2023)
The influence of the quality of home care services on patient satisfaction is an important aspect in the world of health services. Home care is a health service provided by medical personnel or other health professionals in the patient's home, usually to patients who need long-term care or patients with health conditions that make it impossible to come to a health facility. The study aims to determine the effect of the quality of home care services on patient satisfaction. Quantitative descriptive research design with analytical survey type using crosssectional survey approach. The results showed the quality-of-service p value 0.001, home care service p value 0.008, patient satisfaction p value 0.000, patient trust variables with significant values 0.000 < 0.005. It can be concluded that patient trust has a very important role in influencing the level of patient satisfaction and is likely to affect the quality of home care services. Psychologically, it will also affect the level of trust in the institution and service products. Home Care is needed by the community as a form of attention and concern for health workers to residents or communities in need